Identifikasi Zona Potensi Air Tanah Di Desa Batulappa Kec. Patimpeng Kab. Bone - LM Yazid Amsah; Sarman Sarman; Anna Irada La Ode Malim; Surianti Surianti; Asrim Asrim; L.M. Hilman Kurnia (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Water issues are always interesting to be discussed further, because water is one of the main basic needs for humans. This community service activity aims to: (1) Provide information to the community regarding the availability of groundwater potential zones; (2) Provide recommendations for the depth of groundwater drilling. This activity is motivated by the fact that most people in Bone Regency, South Sulawesi Province still rely on shallow groundwater (dug wells) to meet their clean water needs. The method used is the geoelectric method where data is taken directly in the field, from the measurement data then an analysis is carried out to determine the presence of groundwater potential zones in Batulappa Village, Patimpeng District, Bone Regency.